Artificial Intelligence Control of a Magnetic Levitation System - BAKHTAOUI Fayza; KHECHAI Iness; ENCA/ LOUKAL Keltoum (University of M’Sila, 2025)
This work presents an intelligent control approach applied to a magnetic levitation system using PID, Type-1, and Type-2 Fuzzy Logic Controllers. The main objective is to enhance the system’s stability and response under uncertain and noisy conditions. Simulations are conducted using MATLAB/Simulink to validate the performance of each control technique. The results show that Type-2 Fuzzy Logic offers superior dynamic performance, especially in the presence of disturbances and uncertainties.
Keywords: Magnetic Levitation; PID; Fuzzy Logic; Type-1; Type-2; Intelligent Control; MATLAB; Simulink.